Production De Plants De Bananier Plantain Musa AAB Var. Orishele Par La Méthode DESHYPIF À Partir Des Rejet-Écailles Et Rejets Baïonnettes - Denise, Boye Mambé Auguste; Faustin, Soko Dago; Joël, Lolo Akiapo Landry; Tangui, Akaffou Eric; Justin, Kouadio Yatty (European Scientific Journal, ESJ, 2017)
Plantain is an easy plant to grow. There are many varieties directly exploitable which makes it a plant with economic potential. Banana is one of the most consumed foods by the inhabitants of Côte d’Ivoire. However, banana production in this region remains insufficient. The possibility of creating a banana plantation remains a major problem due to the low availability of "seeds". The introduction of a new method under the name DESHYPIF could both reduce the vegetative cycle and the production cycle while allowing the vegetative propagation of the buds. The aim of our study was to show that the production of banana plants by DESHYPIF technique is possible with the use of buds suckers. The study focused on two types of buds, traditional bayonet discharges and buds suckers. The results showed that buds suckers lose more water (39.34 ± 0.52) than the bayonet (27.15 ± 1.03) in the dehydration phase, however, the water level in the phase of physiological awakening remained the same (5.23 ± 0.01). The rehydration rate was 100 %. For the number of young plants emitted in germination, the buds suckers dehydrated gave a number of individuals (77 ± 2) comparable to those of the bayonets (80±1).